Effect of heifer source on reproductive performance, culling, marketing and profitability for a commercial heifer development program - Lynch, J.M.; Lamb, G.C.; Corah, L.R.; Grieger, David M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A commercial heifer development operation purchased 483 weanling Angus × Hereford heifers from 11 sources. Heifers were fed a common silage-based diet through an initial developmental period and retained or culled based on average daily gain, pelvic area, and disposition . The percentage of heifers culled from each source ranged from 18.1% to 94.7% and were either sold directly through a local sale barn or sent to a feedlot with retained ownership . Estrus was synchronized, and heifers were artificially inseminated (AI) for 30 days followed by 15 days of natural mating. First service conception rates for each source ranged from 0% to 92.3%, whereas overall pregnancy rates for the 45-day breeding season ranged from 81.3% to 100%. When expressed as a percentage of the original heifers purchased from each source, overall pregnancy rates ranged from 5.3% to 80%. Heifers that lost their fetuses were sold for a net loss of $213 per head. Heifers sold as first service AI bred, second service AI bred, and naturally mated netted $160, $129, and $89 per head, respectively. With accurate records, stringent culling practices, and evaluation of cost and performance, producers can optimize profit potential of replacement heifers. Early culling and pregnancy diagnosis also will decrease costs while increasing opportunities to minimize the financial risks.
Keywords: Beef; Replacement heifers; Culling; Artificial insemination; Economics